Indomethacin-induced increase in noradrenaline turnover in some rat organs. - Fredholm, B B (1975)
1 The effect of a prostaglandin synthesis inhibitor, indomethacin, on noradrenaline turnover rate in various rat tissues was determined from the product of the endogenous noradrenaline concentration and of the rate constant of (-)-[3H]-noradrenaline decline after injection of the labelled amine in tracer doses. 2 Treatment of the rats with indomethacin (5 mg/kg p.o. five times during 2.5 days) increased noradrenaline turnover rate 32-36% in submandibular gland, spleen and heart, and 4-17% in epididymal and subcutaneous adipose tissue. 3 The extrapolated [3H]-noradrenaline content at time 0 was greater in heart and adipose tissue of indomethacin-treated animals than in controls, while it was not significantly changed in spleen and salivary gland. 4 There was no apparent relationship between tissue concentrations of intravenously injected [14C]-indomethacin and the effect of indomethacin on noradrenaline uptake and turnover rate in the different tissues. 5 Indomethacin treatment did not affect monoamine oxidase and catechol O-methyl-transferase activities in the different tissues. 6 The results are consistent with the hypothesis that indomethacin increases noradrenaline turnover in the rat by blockade of a locally operating feed back inhibition of transmitter release by prostaglandins. However, additional effects, such as an increased impulse traffic, cannot be ruled out.